Occurrence of Anaplasma sp. infection in pigs (Sus scrofa) at Morgan Farm, Palangka Raya City - Febriyatin, Fierdausi Nur’Aini; Setiawan, Boedi; Yuniarti, Wiwik Misaco; Wibawati, Prima Ayu; Yudhana, Aditya (Universitas Airlangga, 2024)
This research was conducted to identify the occurrence of Anaplasma sp. infection in pigs (Sus scrofa) at Morgan Farm, Pahandut Subdistrict, Palangka Raya City. Palangka Raya City is one of the cities that has great potential to develop pig livestock, but the shortcomings of the farms in Palangka Raya City still apply traditional housing with poor cage sanitation. Samples in this study were obtained from Morgan Farm with a total of 68 pig blood samples, then examined at the Animal Health and Veterinary Public Health Laboratory of Palangka Raya City, then starting with the preparation of PBS solution and making blood review preparations using 10% Giemsa staining. The blood obtained was then reviewed using object glass, absolute methanol, and stained with Giemsa 10%. Identification was carried out using a trinocular microscope with a magnification of 400x and immersion oil was dripped on the object glass. The results of this research showed that 29 pig blood samples were positive out of 68 pig samples, with an occurrence rate of 42.6%. The morphology of Anaplasma sp. found is that there is a round, purplish-blue dot shape at the edge of red blood cells. From these results it can be concluded that the infection of Anaplasma sp. in pigs (Sus scrofa) at Morgan Farm, Pahandut District, Palangka Raya City is 42.6%, which means that the infection is very high for Palangka Raya City.